Analisis Kesalahan Mahasiswa Pendidikan Matematika Unimed dalam Menyelesaikan Soal Induksi Matematika - Dinda Indriani Nasution; Maisyaroh Maisyaroh; Afrizal Manurung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the difficulties of mathematics education students in solving mathematical induction problems in terms of concept understanding and calculation aspects. This type of research is descriptive using a qualitative approach. Based on the results of data processing, conclusions can be drawn, namely: (1) Concept errors, namely errors made by students because they do not understand the concept well. (2) Strategy error, which is an error that occurs because students choose the wrong way to work. (3) Calculation errors, namely errors in performing mathematical operations. Systematic errors, which are errors related to the wrong selection of extrapolation techniques. (4) Of the 10 mathematics education students, the data description of the research results shows an average in the normal category, namely 53%. Translated with DeepL.com (free version).